The role of accessibility for regional innovation systems - Martin Andersson; Charlie Karlsson (European Regional Science Association (ERSA), 2002)
The link between proximity and innovation has been dwelled upon extensively in the literature. A regional economic milieu characterized by proximity between relevant actors is maintained to be suitable for establishing and maintaining successful regional innovation system. In this paper it is proposed that the relevant link to be studied is rather that between accessibility and innovation. Although accessibility is a key factor in facilitating the processes stressed to be important for innovations, the relationship between accessibility and innovation is surprisingly unexploited. Scrutinization of the relationship between accessibility and innovation is necessary in order to fully comprehend regional innovative capacity. Furthermore, such scrutinization will shed further light in the issue of the importance of knolwedge spillovers.
Keywords: 330